Cultural industries in Latin America and the Caribbean : challenges and opportunities - Quartesan, Alessandra (IDB [Washington]US, 2007)
Demonstrates the value and the potential for cultural industries in the Latin American and Caribbean economy. Identifies the need for a comprehensive approach, structured policies, and targeted interventions aimed at improving the conditions and prospects of these industries.